Auden's Apologies for Poetry. - McDiarmid, Lucy (Princeton legacy library., 2014)
Common wisdom has it that when Auden left England for New York in January 1939, he had already written his best poems. He left behind (most critics believe) all the idealisms of the 1930s and all serious concerns to become an unserious poet, a writer of ingenious, agreeable, minor lyrics. Lucy McDiarmid argues that such readers, spoiled by the simple intensities of apocalypse, distort and misjudge Auden's greatest work. She shows that once Auden was freed from the obligation to criticize and reform the society of his native country, he devoted his imaginative energies to commentary on art.